Upstream Open Reading Frames Located in the Leader of Protein Kinase Mζ mRNA Regulate Its Translation - Bal, Natalia V.; Susorov, Denis; Chesnokova, Ekaterina; Kasianov, Artem; Mikhailova, Tatiana; Alkalaeva, Elena; Balaban, Pavel M.; Kolosov, Peter (Frontiers in Molecular Neuroscience, 2016)
For protein synthesis that occurs locally in dendrites, the translational control mechanisms are much more important for neuronal functioning than the transcription levels. Here, we show that uORFs (upstream open reading frames) in the 5’ untranslated region (5’UTR) play a critical role in regulation of the translation of protein kinase Mζ (PKMζ). Elimination of these uORFs activates translation of the reporter protein in vitro and in primary cultures of rat hippocampal neurons. Using cell-free translation systems, we demonstrate that translational initiation complexes are formed only on uORFs. Further, we address the mechanism of translational repression of PKMζ translation, by uORFs. We observed an increase in translation of the reporter protein under the control of PKMζ leader in neuronal culture during nonspecific activation by picrotoxin. We also show that such a mechanism is similar to the mechanism seen in cell stress, as application of sodium arsenite to neuron cultures induced translation of mRNA carrying PKMζ 5’UTR similarly to picrotoxin activation. Therefore, we suppose that phosphorylation of eIF2a, like in cell stress, is a main regulator of PKMζ translation. Altogether, our findings considerably extend our understanding of the role of uORF in regulation of PKMζ translation in activated neurons, important at early stages of LTP.